Differences in levels of knowledge of FSTP students (Faculty of Science, Technology, and Education) and FEB (Faculty of Economics and Business) Muhammadiyah Lamongan University about criteria halal of skincare products - Febrianti, Krisma; Handayani, Riana Prastiwi; Mahaputra Kusuma Negara, Sri Bintang Sahara; Kusumo, Djati Wulan (Universitas Airlangga, 2024)
Skincare has become a daily necessity for students especially Muslims, who must pay attention to the halalness of the skincare products used, because it has been regulated in Islam regarding halal and haram consumption. Student knowledge greatly influences halal in the selection of skincare products to be used. This study aims to determine the difference in the level of knowledge of FSTP and FEB students at Muhammadiyah Lamongan University. The research design used is descriptive comparative with purposive sampling technique. Data collection was carried out prospectively, from collecting questionnaire data that met the inclusion and exclusion criteria. The research instrument used was a closed questionnaire consisting of respondents' personal data and statements related to the criteria for halal skincare products. The results obtained from this study are the level of knowledge in the good category at FSTP as much as 60.52% and FEB as much as 76.6%, the sufficient category at FSTP as much as 38.6% and FEB as much as 21.28%, the poor category at FSTP as much as 0 .88% and FEB as much as 1.12%. The data obtained was then processed using SPSS with the Mann Whitney Test and obtained a p-value of 0.063 (> 0.05). In conclusion, there is a significant difference between the level of knowledge of FSTP and FEB regarding the criteria for halal skincare products.